Tahlili Study of the Practice Most Loved by Allah - Badani Tempo, Rachmat (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
This paper discusses the practice that is most loved by Allah, by using the form of tahlili hadith to the hadits of ‘Aisyah. It can be understood that Rasulullah stipulates a middle attitude in doing good deeds to the extent of one’s ability that he can do continuously, because the practice is most loved by Allah is a practice tha is done continuously even if it’s a little. This is what the prophet Muhammad taught as narrated from other hadiths that his practice is always done continuously. This hadith also explains the prohibition of breaking someone from the practice he is doing, by him Rasulullah. Encourages his people to do a little practice so as not to burden someone and not make him feel bored so that he can continue to do it continuously.